Residential greenness and risk of prostate cancer: A case-control study in Montreal, Canada - Claire Demoury; Benoît Thierry; Hugues Richard; Brittany Sigler; Yan Kestens; Marie-Elise Parent (Environment International, 2017)
Background: Recent studies suggest that exposure to greenness favors several health outcomes. We assessed whether living in the proximity of greener areas was related to prostate cancer incidence in a population-based case-control study in Montreal, Canada. Materials and methods: Interviews eliciting lifetime addresses were conducted with 1933 prostate cancer cases diagnosed in 2005–2009 and 1994 population controls. Odds ratios (OR) and 95% confidence intervals (CI) estimated the association between residential greenness, both at recruitment (2005–2009) and about ten years prior (1996), defined by the normalized difference vegetation index (NDVI) around the home, and prostate cancer risk. Three models were developed adjusting for age, individual characteristics, and individual and ecological characteristics, estimating relative risk in relation to an interquartile range (IQR) increase of the NDVI. Results: We observed inverse associations between greenness measured within home buffers of 150 m, 300 m, 500 m and 1000 m, at both time points, and risk of prostate cancer, independently of individual and ecological characteristics. For instance, using a buffer of 300 m, the OR for an IQR increase of 0.11 in NDVI at the time of recruitment was 0.82 (95%CI 0.74–0.92). The corresponding OR for an IQR increase of 0.15 in NDVI in 1996 was 0.86 (95%CI 0.74–1.00). There were little differences in risks according to buffer size, the time point of exposure, when considering prostate cancer aggressiveness, or when restricting controls to men recently screened for prostate cancer to reduce the likelihood of undiagnosed cancer among them. Conclusion: Men living in greener areas, either recently or about a decade earlier, had lower risks of prostate cancer, independently of socio-demographic and lifestyle factors. These observations are novel and require confirmation. Keywords: Prostate cancer, Greenness, Case-control study, GIS, Environment